What do standard radiography and clinical examination tell about the shoulder with cuff tear arthropathy? - Favard Luc (Journal of Orthopaedic Surgery and Research, 2011)
Abstract Background This study evaluates the preoperative conventional anteroposterior radiography and clinical testing in non-operated patients with cuff tear arthropathy. It analyses the radiological findings in relation to the status of the rotator cuff and clinical status as also the clinical testing in relation to the rotator cuff quality. The aim of the study is to define the usefulness of radiography and clinical examination in cuff tear arthropathy. Methods This study analyses the preoperative radiological (AP-view, (Artro-)CT-scan or MRI-scan) and clinical characteristics (Constant-Murley-score plus active and passive mobility testing) and the peroperative findings in a cohort of 307 patients. These patients were part of a multicenter, retrospective, consecutive study of the French Orthopaedic Society (SOFCOT-2006). All patients had no surgical antecedents and were all treated with prosthetic shoulder surgery for a painful irreparable cuff tear arthropathy (reverse-(84%) or hemi-(8%) or double cup-bipolar prosthesis (8%)). Results A positive significancy could be found for the relationship between clinical testing and the rotator cuff quality; between acromiohumeral distance and posterior rotator cuff quality; between femoralization and posterior rotator cuff quality. Conclusion A conventional antero-posterior radiograph can not provide any predictive information on the clinical status of the patient. The subscapular muscle can be well tested by the press belly test and the teres minor muscle can be well tested by the hornblower' sign and by the exorotation lag signs. The upward migration index and the presence of femoralization are good indicators for the evaluation of the posterior rotator cuff. An inferior coracoid tip positioning suggests rotator cuff disease.